Spatial Issues and Covid-19 Dispersion in Small Cities of The Amazon River Delta - Costa, Sandra Maria Fonseca da; Lima, Viviana Mendes; Carmos, Monique Bruna Silva do; Montoia, Gustavo Rodrigo Milaré (National Journal of City Management, 2021)
The COVID - 19 virus emerged in China and has spread to all areas in Brazil, including the Amazon River Delta, where the population lacks essential services. Thus, this article aims to characterize the dispersion of COVID-19 in the small municipalities of the Amazon River Delta, which have fewer than 50,000 inhabitants, detailing the towns’ situation. Covid-19 data provided by the health departments of the states of Amapá and Pará, and census data from the IBGE, were used to create maps of the disease for the Delta’s municipalities. The virus circulated rapidly to the smallest localities, where the health service and sanitary conditions are precarious, leading to a severe contamination rate. Together with other known aspects, this is yet another opportunity to show the regional needs and the importance of public policies for this population.